The Impact of Covid-19 on International Student Support: A Global Perspective - Bardill Moscaritolo, Lisa; Perozzi, Brett; Schreiber, Birgit; Luescher, Thierry (Journal of International Students, 2021)
The COVID-19 pandemic caused unique challenges to international students. Student Affairs and Services (SAS) across the higher education sector played a key role in supporting students and institutions during the pandemic. This article reports the findings of an exploratory survey with SAS practitioners from around the globe on the ways in which SAS responded to the pandemic and sought to mitigate the impact of the pandemic on students in general and international students specifically. The results demonstrate that international students were among the primary groups of students impacted by the pandemic. Specific challenges identified include mental wellbeing, inability to return home, financial hardships, fear, and uncertainty. Discrimination of certain groups was also noted. SAS intervened to assist international students in navigating these challenges across world regions, including services declared essential for international student support. Finally, financial implications and the future of international student support are explored.